The slippery slope - Snicket, Lemony; Helquist, Brett (London : Egmont Books, 2004)
In the perilous Mortmain Mountains, Klaus and Violet Baudelaire meet another well-read person, who helps them try to rescue Sunny from the villainous Count Olaf and his henchmen as they all near "the last safe place.".
Includes audiobook.
Keywords: Humorous fiction; Orphans -- Fiction